Continuous combined microwave and hot air treatment of apples for fruit fly (Bactrocera tryoni and B. jarvisi) disinfestation. (May 2015) - Gamage, T.V.; Sanguansri, P.; Swiergon, P.; Eelkema, M.; Wyatt, P.; Leach, P.; Alexander, D.L.J.; Knoerzer, K.
Abstract: Apples at 24 ± 2 °C were heated in a pilot scale hot air assisted (40 °C) continuous pentagonal microwave system, to evaluate the effectiveness of this treatment on insect mortality (variety Mutsu) and fruit quality (variety Granny Smith). An average temperature of 53.4 ± 1.3 °C at core, bottom and flesh of the apple was recorded at the end of the treatment. One hundred percent mortality of the most tolerant stage of Queensland fruit fly ( Bactrocera tryoni, Froggatt) and Jarvis's fruit fly ( Bactrocera jarvisi, Tryon), were observed when the Mortality value (M52, equivalent time of isothermal treatment at 52 °C) at the slowest heating point applicable for each experiment was ≥ 50 min and ≥ 37 min, respectively. Results: showed that microwave heat treatment is effective for insect disinfestation without any adverse impact on total soluble solids, flesh or peel firmness of the treated apples. The treated apples recorded a significantly higher pH and lower ion leakage than the untreated apples after 3 or 4 weeks. Therefore, the microwave heat treatment has the potential to be developed as an alternative chemical free quarantine treatment against economically significant insect pests. Industrial relevance: Hot air assisted microwave heating of fruits and vegetables, is more cost effective compared to vapour heat treatment and ionising radiation for disinfestation of insects. Microwave treatment is environmentally friendly compared to fumigation and chemical treatments. Hot air assisted microwave disinfestation can be performed at farms or centralised pack houses since the capital cost would be comparatively lower than vapour heat or ionising radiation treatments. Highlights: Apples were heated in a pilot scale hot air assisted continuous pentagonal microwave system. We evaluated the effectiveness of microwave treatment on insect mortality and fruit quality. Microwave treatment effectively disinfested insects and had no adverse impact on apple quality. Microwave treatment could be a potential alternative chemical free quarantine treatment.